Thermo-Environmental Performance Analysis of Cascade Refrigeration System on Cruise Ship Applications - Natasya, Deva; Rayhan, Fajri Ashfi (International Journal of Marine Engineering Innovation and Research, 2026)
This study analyzes the thermo-environmental performance of cascade refrigeration systems applied to cruise ships to support energy efficiency improvement and emission reduction in accordance with MARPOL Annex VI regulations. Cruise ships have high energy demands, particularly in cooling systems that significantly contribute to overall energy consumption and environmental impact. This research aims to evaluate the effect of operating parameters and refrigerant selection on system performance using exergy efficiency, Ecological Coefficient of Performance (ECOP), and Total Equivalent Warming Impact (TEWI) as evaluation indicators. A thermodynamic model based on mass, energy, and exergy balance equations is applied, with simulations conducted under various operating temperatures and refrigerant combinations. The results indicate that increasing operating temperature from 275 K to 295 K reduces exergy efficiency and ECOP due to increased irreversibility, while TEWI rises significantly as a result of higher energy consumption. Hydrocarbon refrigerants such as R600a/R290 and R152a/R290 show the best performance in terms of both energy efficiency and environmental impact. In contrast, CO₂-based combinations tend to exhibit lower efficiency and higher environmental impact under certain conditions. Overall, selecting appropriate refrigerants and optimizing operating conditions are essential to achieve a balance between system efficiency and environmental sustainability in marine refrigeration systems.